Lumber Camp, 1891 - Pickford, Joel:::::::::
George Pickford, 30 and his son Rollin Sr., 4 (the artist's father) with a group of friends visiting a lumber operation during a mountain outing in 1891. The second digital image shows a closeup detail of the travelers, with George Pickford and son in the center.